Analysis of the Possibility of Fraud in the National Health Insurance Program in Indonesia - Purwanti Agustini; Romauli Veranica; Dickson Dickson; Erlina Puspitaloka Mahadewi (CV. Inara, 2025)
The study focused on the purpose of finding out the effect and covering fraud in the National Health Insurance. Fraud is an act carried out intentionally to gain financial gain from the JKN program in the National Social Security System, through fraudulent acts that are not in accordance with the provisions of laws and regulations. Health fraud is a serious threat to the world, causing financial misuse of scarce resources and negative impacts on access to health, infrastructure, and social determinants of health. In Indonesia, cases of fraud continue to increase from year to year. The purpose of this study is to find out the latest studies related to the analysis of the opportunities for fraud in health insurance, and how the mechanism for effective prevention and mitigation efforts can be implemented in the implementation of the Health Insurance program in Indonesia. The method used in this journal uses qualitative descriptive through a literature study approach. Opportunities for fraud practices in JKN can be identity falsification, collusion to make false claims, unnecessary health care, excessive invoices, deviations or upcoding of diagnosis codes, document discrepancies, and duplicate claims. The reasons for fraud that usually occur are known as the fraud triangle, namely motivation, opportunity, and rationalization. Result of this study suggested systematic prevention efforts are needed together by health service providers, BPJS, and the Government by implementing the principles of a fraud prevention system, and the formation of a fraud prevention team that is adjusted to the needs for scale of the organization and national, in the future to reduce the negative impacts that occur.